Educational Challenges and Islamic Values in the Age of Disruption - Hadiamsyah, Yudhi; Meidina, Ahmad Rezy (Interdisciplinary Journal of Social Science and Education (IJSSE), 2024)
The era of disruption, marked by technological advances and digitalisation, has brought significant changes in various aspects of life, including education. In the Indonesian context, education is faced with the challenge of maintaining Islamic values amidst globalisation and digitalisation. This article discusses how the education system must adapt to the changes that are taking place, with a focus on efforts to maintain Islamic values that have begun to fade in the midst of the digital era. The main challenges include curriculum changes, innovative learning methods, and negative influences from the internet, such as moral decline and technology dependency. On the other hand, disruption also provides opportunities, such as the digitisation of learning through platforms like YouTube, which facilitates wider access to education. In conclusion, education must be able to combine technological advancement with the preservation of Islamic values to achieve ideal national goals.